A ciberpolítica na disputa presidencial brasileira de 2018 no Twitter - Machado, Lisandro Lemos (2024)
The thesis addresses the incorporation of digital social networks by the political field, notably in electoral periods, amplifying and providing opportunities for new forms of what is historically envisioned as an electoral campaign, constituting a transversal way of doing politics, cyberpolitics. The focus is on the 2018 Brazilian presidential election, in which the use of digital social networks had an impact throughout the process - which also took place in the wake of previous events, such as the US presidential elections of Barack Obama (2008) and Donald Trump (2016) -, in the historical role of understanding the context and dynamics involved. Positioned in the History of the Present Time, combined with Political History, in the line of Politics and Power Relations, the research is based on publications on the digital social network Twitter, during the electoral campaign, analyzing the profiles of the two most voted parties in the 2018 presidential election, PSL and PT, as well as the profiles of its candidates, Jair Bolsonaro and Fernando Haddad, which constitute the primary source of research, from the perspective of the elements involved in the concepts of cyberpolitics (Bruzzone), content analysis (Bardin) and political discourse (Charaudeau). The general objective is to identify the elements involved in the political discourse from the use of the referred network by both the political parties and their respective candidates, intending, in this way, to contribute with the historiography referring to the political processes and relationship of power in cyberpolitics. The identification takes place through content and discourse analysis of the publications obtained from the aforementioned profiles, seeking to draw a parallel between the behavior between party officials and candidates' individuals, referring to their discursive strategies and the impact on electoral engagement. For that, aspects of the Internet are presented, related to the deterritorialization process it promotes, as well as its role as a means of communication through its social networks. Elements of content analysis and political discourse are raised, which base the analysis of primary sources, as well as the identification and quantification of voter engagement, referring to the format of the content produced and the survey of established interactions. Finally, the classification is carried out according to the evidence arguments. It was possible to confirm the capacity for personification that digital social networks allow, with the campaigns developed by candidates managing to obtain significantly greater engagement when compared to those carried out by parties. The winning candidate of the election proved to be ahead of all the others in terms of results obtained.